URGENSI PENGGUNAAN TELEX RELEASE DALAM PROSES PENYELENGGARAAN PENGANGKUTAN BARANG MELALUI LAUT DI INDONESIA: THE URGENCE OF USING TELEX RELEASE IN THE PROCESS OF ORGANIZING THE TRANSPORTATION OF GOODS THROUGH SEA IN INDONESIA - Salfia Putri Sakina; Isis Ikhwansyah; Purnama Trisnamansyah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Indonesia is one of the countries that has implemented the telex release process in the implementation of the transportation of goods by sea. Telex release is the process of digitizing the bill of lading because the delivery of the document is sent via email from the carrier to the sender. However, the regulations governing the operation of sea transportation in Indonesia have not explicitly accommodated telex releases, even though in practice telex releases have been used in the implementation of sea transportation in Indonesia. Efforts that can be made to optimize the use of telex releases are by accommodating the principles contained in international instruments related to sea transportation law, making rules and norms related to the use of telex releases, considering Indonesia's membership in international organizations in the field of sea transportation, and creating the process of organizing sea transportation in Indonesia becomes more effective and efficient through the use of telex releases.